Sistem Pendukung Keputusan Seleksi Penerimaan Karyawan Rumah Sakit Bmc Dengan Menggunakan Metode Promethee - Iqbal, Iqbal; Juliansyah, Rommi (Fakultas Ilmu Komputer Universitas Almuslim Bireuen - Aceh, 2023)
The improvement in the quality and quality of service is also very large driven by the availability of functional human resources (HR) in their respective work positions or on their respective job lists. Bireuen Regency. Considering that recently there have been very rapid growth of several other health service institutions/agencies in Bireuen District, so the quality of human resources must be given great attention. Selection of new employees at the Bireuen Medical Center (BMC) hospital is carried out manually by examining administrative files and giving an assessment weight to each prospective employee who applies for a job position provided by the BMC Hospital. The decision support system for hiring new employees at the Bireuen Medical Center (BMC) Hospital in Bireuen Regency is a system that can provide decisions based on ranking results that have been calculated using the promethee method, where in a system designed by users who have the authority to make decisions, they can input data. -data on assessment criteria and parameters, then determines the assessment parameters for each alternative applicant with the weights that have been applied so that the system then provides a ranking of all alternatives to assist the user in making decisions on alternatives that will be accepted as employees at the Bireuen Medical Center hospital (BMC)